Fuzzy Based Efficient Routing Protocol For Route Recovery In MANET (International Journal of Engineering and Computer Science, 2017)
A Mobile Ad-Hoc Network (MANET) is a collection of wireless mobile hosts that are arbitrarily located and lack any infrastructure and centralized administration. In MANET, routing protocols are used to provide the specific path for sending the data packets. By growing the use of real-time application on mobile devices, there is a constant challenge to provide reliable and high quality routing algorithm among these devices. Due to the mobile nature of MANET, all the routing protocols have some route errors. In addition to limited energy resources, failure of the nodes is a constraint to provide a reliable communication in wireless mobile networks. The failure of a node may have many reasons like mobility of the node and node or link failure. In this paper, we propose a technique to improve routing protocols by considering both energy and failure constraints and managing them. By using the proposed protocol, the routing protocols dynamically adapt to node’s failure. In this paper, we propose a fuzzy based efficient routing protocol (FBERP) for large scale mobile ad-hoc networks that aims to minimize the packet loss rate. Each node in the network is characterized by its communication parameters. We develop a fuzzy logic controller that combines these parameters, Packet Loss Rate, Communication Rate, Energy and Delay Parameters. The value obtained, indicates the priority of a node and it is used in route formation. Our simulation shows that our proposed protocol outperforms the standard AOMDV routing protocol in minimizing the packet loss.